2000
DOI: 10.1159/000014266
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Home Monitoring for Infants Discharged with Apnea of Prematurity

Abstract: Sixty-four preterm infants with apnea of prematurity (AOP) discharged with cardiorespiratory home monitoring (HM) were prospectively followed. For each monitor alarm the parents recorded the occurrence of apnea, bradycardia or color change, and the type of assistance provided. The mean gestational age at birth was 28.8 (26–34) weeks, and the mean birth weight was 1,180 (730–2,390) g. The parents of 61/64 infants (95%) reported a total of 185 true AOPs with a mean of 3 (1–12) events/infant. The mean postconcept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
0
6
1
1
Order By: Relevance
“…The mean GA of the study population at birth was 28.8 wk, and the mean birthweight was 1.2 kg. AOP ceased at 40–44 weeks GA in 80% of the neonates, and this study found no clear correlation between the degree of prematurity and the age at the last apnoeic event 20 …”
Section: Commentcontrasting
confidence: 76%
See 1 more Smart Citation
“…The mean GA of the study population at birth was 28.8 wk, and the mean birthweight was 1.2 kg. AOP ceased at 40–44 weeks GA in 80% of the neonates, and this study found no clear correlation between the degree of prematurity and the age at the last apnoeic event 20 …”
Section: Commentcontrasting
confidence: 76%
“…AOP ceased at 40-44 weeks GA in 80% of the neonates, and this study found no clear correlation between the degree of prematurity and the age at the last apnoeic event. 20…”
Section: Gestational Agementioning
confidence: 99%
“…Once the alarm sounds to alert the parents to a possible AOP episode, tactile stimulation may be required, and the cardiorespiratory monitor will record the event in an electronic log [14]. While the monitors record each AOP event electronically, parents must also manually document details, such as visible signs of distress or color change [7,15]. This reliance on manual logging and interpretation can cause undue stress and excess mental burden for parents [15].…”
Section: Search Resultsmentioning
confidence: 99%
“…Tauman and Sivan (11) in their study concluded that there was an association between neonatal apnea and prematurity. The same observation was reported by Malviya et al (12) .…”
Section: Discussionmentioning
confidence: 98%